On the problem of effects of divorce on children - Dovydaitytė, M. (Psichologija, 1995)
The present article describes the research on effects of parental divorce on children. Retrospective study of effects of divorce on children was conducted. The results indicate that children reactions to parental divorce are emotional and physical distancing from the situation, hypercompensation, delinquent behaviour patterns, and problems of communication with opposite sex as well as psychosomatic reaction. However divorce can be experienced as positive or neutral life event. If a child evaluates parent negatively the negative effects of divorce seem to be less. The most dramatically experienced effects on children are in loyalty conflict situation.